MATRIX: a platform for cultivation profiling and bioactive discovery in natural product research - Khalil, Zeinab G.; Sritharan, Thulasi; Salim, Angela A.; Capon, Robert J. (Frontiers in Natural Products, 2025)
The MATRIX protocol presents a novel miniaturized 24-well plate approach for microbial cultivation profiling, enabling the efficient and parallel assessment of microbial metabolite production. This method integrates a media MATRIX within a microbioreactor to facilitate the creation of diverse growth conditions for microbial cultivation. The 24-well format supports the simultaneous study of multiple microbial strains and conditions, allowing the discovery of novel bioactive compounds. By employing a variety of media compositions and cultivations, MATRIX enhances the understanding of microbial metabolic pathways and interactions. This protocol provides a robust platform for natural product discovery, microbial ecology studies, and drug development, showcasing its potential to uncover new natural products and other valuable bioactives. The MATRIX approach offers a resource-efficient platform for microbial biodiscovery, contributing significantly to natural product research and drug development.